2010
DOI: 10.1007/s11668-010-9352-9
|View full text |Cite
|
Sign up to set email alerts
|

Failure Analysis of AISI-304 Stainless Steel Styrene Storage Tank

Abstract: This paper presents the failure analysis of AISI-304 stainless steel tank that was fabricated by welding and used for the storage of styrene monomers. After about 13 years of satisfactory operation, significant cracking was observed adjacent to the weld joints and in base plate near tank foundation. Weld repair was by shielded gas arc welding using AISI 308 stainless steel filler wire. The failed base plate was replaced with the new AISI 304 base plate of same thickness. After a short period of time, seepage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The investigations revealed that these cracks appeared because of IGC. 6 The austenitic SS was used as a tube material in steam generators for the purpose of increasing its lifetime instead of conventional materials. But after 6 months, corrosion takes place also in welded joints of SS, which results in the leakage of tubes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigations revealed that these cracks appeared because of IGC. 6 The austenitic SS was used as a tube material in steam generators for the purpose of increasing its lifetime instead of conventional materials. But after 6 months, corrosion takes place also in welded joints of SS, which results in the leakage of tubes.…”
Section: Introductionmentioning
confidence: 99%
“…This is because carbide precipitation requires some time, as adjacent to the fusion line material senses maximum temperature and cooling rate. 6,7 Various researchers have used many approaches to stop the IGC after welding.…”
Section: Introductionmentioning
confidence: 99%